PKM : Implementasi Teknologi Akuntansi Pada Koperasi Sekolah Untuk Meningkatkan Akuntabilitas Keuangan - Kaslani; Fathurrohman; Ryan Hamonangan; Farra Oktaviani Putri; Mochammad Rifqi Aqila (CV. Multi Kreasi Media, 2024)
School cooperatives play a crucial role in managing finances and providing economic benefits to their members. However, school cooperatives often face challenges in maintaining good financial accountability due to limited use of accounting technology. This issue can lead to inaccuracies in financial records and decrease members' trust in the cooperative. This program aims to enhance the financial accountability of school cooperatives through the implementation of appropriate accounting technology. The methods employed include training on accounting software and mentoring in the application of the system. The expected outcome is an improvement in the accuracy and transparency of the cooperative's financial management, ultimately increasing member trust and operational efficiency.